Girl of the Southern Sea - Kadarusman, Michelle, 1969- (Toronto, Ontario Canada : Pajama Press, 2019)
Nia, who dreams of an education and the chance at a better life, must battle the dangers of local superstition and thwart her father's plans for her future.
Junior Library Guild
Ages 11-14.
Grades 6-9.
660L
A Junior Library Guild selection (JLG)
Keywords: Fathers and daughters -- Juvenile fiction; Poor families -- Juvenile fiction. -- Indonesia; Superstition -- Juvenile fiction; Fathers and daughters -- Fiction; Poor -- Fiction; Superstition -- Fiction; Father-daughter relationship -- Fiction; Poor -- Fiction; Superstition -- Fiction; Jakarta (Indonesia) -- Juvenile fiction; Jakarta (Indonesia) -- Fiction; Jakarta (Indonesia) -- Fiction